Effects of different concentrations of butyrate on microbial community construction and metabolic pathways in anaerobic digestion. (June 2023) - Xu, Yonghua; Meng, Xianghui; Song, Yunong; Lv, Xiaoyi; Sun, Yong
Graphical abstract: Highlights: At OLR of 3.6 g/(L·d), butyrate was efficiently degraded with VBP of 1.50 L/(L·d). Functional microorganisms were Methanosarcina, Syntrophomonas, and Lentimicrobium . The hydrolysis and acidogenesis stage occurred with butyrate as sole substrate. Hydrogenotrophic methanogenesis was the main pathway to consume H2 . Abstract: Investigating the effect of butyric acid concentration on anaerobic digestion systems in complex systems is important for the efficient degradation of butyric acid and improving the efficiency of anaerobic digestion. In this study, different loadings of butyric acid with 2.8, 3.2, and 3.6 g/(L·d) were added to the anaerobic reactor. At a high organic loading rate of 3.6 g/(L·d), methane was efficiently produced with VBP (Volumetric Biogas Production) of 1.50 L/(L·d) and biogas content between 65% and 75%. VFAs concentration remained below 2000 mg/L. Metagenome sequencing revealed changes in the functional flora within different stages. Methanosarcina, Syntrophomonas, and Lentimicrobium were the main and functional microorganisms. That the relative abundance of methanogens exceeded 35% and methanogenic metabolic pathways were increased indicated the methanogenic capacity of the system significantly improved. The presence of a large number of hydrolytic acid-producing bacteria also indicated the importance of the hydrolytic acid-producing stage in the system.